Анализ электромагнитной совместимости на нефтеперекачивающих станциях - Абдельшафи, Исам М. А. (НТУ "ХПИ", 2014)
В статье рассмотрена проблема обеспечения электромагнитной совместимости на нефтеперекачивающих станциях – объектах с жесткой электромагнитной обстановкой. Отсутствие нормативной базы по ЭМС для таких объектов приводит к тому, что не реализуется системный подход к защите от опасных электромагнитных воздействий. Проведен анализ источников и приемников электромагнитных воздействий, возможных рисков и последствий из-за несоблюдения электромагнитной совместимости.

In the article the problem of ensuring electromagnetic compatibility of hectare oil pumping stations is considered. Lack of regulatory framework EMC for such objects leads to what is not realized systematic approach toprotection from hazardous electromagnetic influences. The analysis of sources and receivers of electromagnetic influences, possible risks and consequences because of non-compliance with electromagnetic compatibility is carried out. It consists of such remotely controlled power supplies for anode discharge, ion extraction and focusing of the extracted ion beam and power supplies for control of gas feed system. The power supply and control system of the multi-charged ions injector satisfies the requirements and ensures the stable injector operation.
The analysis of electromagnetic compatibility on oil pumping stations
Keywords: электромагнитная обстановка; нормативная база; ЭМС; электромагнитные воздействия; electromagnetic compatibility; oil pumping station